2006
DOI: 10.1111/j.1365-2605.2006.00682.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual behaviour, sperm quantity and quality after short‐term streptozotocin‐induced hyperglycaemia in rats

Abstract: Studies of diabetes mellitus in the streptozotocin rat model suggest that sexual dysfunctions may result from diabetes-induced alterations of the neuroendocrine-reproductive tract axis. Our investigation was performed to better define the effects of short-term hyperglycaemia on rat epididymal sperm quantity, quality and transit time, using both natural mating and artificial in utero insemination protocols. Male rats were made diabetic with streptozotocin (sc, 40 mg/kg), whereas controls received vehicle. Sexua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

34
137
2
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(183 citation statements)
references
References 27 publications
34
137
2
5
Order By: Relevance
“…Although, the serum testosterone level declined significantly at the end of 36 days in STZ treated group, subsequent estimation on 72 day did not show any difference between control and diabetic groups. The review of earlier studies on the effect of hyperglycemia on plasma testosterone level has demonstrated conflicting results [16][17][18][19] possibly due to differences in study models and diabetes induction methods. With the decline in testosterone level at 36 days interval, we speculated an aberrant spermatogenesis in diabetic animals.…”
Section: Discussionmentioning
confidence: 99%
“…Although, the serum testosterone level declined significantly at the end of 36 days in STZ treated group, subsequent estimation on 72 day did not show any difference between control and diabetic groups. The review of earlier studies on the effect of hyperglycemia on plasma testosterone level has demonstrated conflicting results [16][17][18][19] possibly due to differences in study models and diabetes induction methods. With the decline in testosterone level at 36 days interval, we speculated an aberrant spermatogenesis in diabetic animals.…”
Section: Discussionmentioning
confidence: 99%
“…8 Epidemiological evidences emphasize that oxidative stress plays an important role in the etiology of male infertility. 9 Our recent findings in STZ-diabetic adult rodent models have shown the occurrence of oxidative stress in the testis during acute phase and its progression.…”
Section: Introductionmentioning
confidence: 99%
“…Streptozotocin induced diabetes in male rats resulted atrophy of sex organ, changes in histoarchitecture of ventral prostate, diminution in sperm count (Sing et al, 2005), along with low levels in plasma gonadotrophins (Seethalakshmi et al, 1987) and testosterone (Sanguinetti et al, 1985). The copulatory behavior of diabetic rat has been collapsed along with low fertility in induced normal mating (Scarano et al, 2006). In human, diabetes is associated with erectile dysfunction (Takahashi et al, 1997) along with loss of libido and abnormal morphology of sperm, low plasma levels of gonadotrophins and testosterone (Dinulvic et al, 1990).…”
Section: Introductionmentioning
confidence: 99%